Customer awareness towards hyrdoponic / Johan Iskandar Kamarudin - Kamarudin, Johan Iskandar (Faculty of Business and Management, 2009)
Kazzponic Sdn Bhd is an organization founded by a bumiputra which operates in selling liquid fertilizer and hydroponics set and services. The company is striving hard to survive in the market that is increasing of competition. During the industrial training, it is found that most of that the company is very lack in a certain areas. One of the most significant areas is that they are lack of utilize the promotion mix. Promotional mix is currently the most important strategic tools taken by most successful companies in the market. The promotion mix which are comprises advertising, personal selling, sales promotion and public relation. The purpose of the study is to know whether Kazzponic Sdn. Bhd adopting any promotional mix and also which promotional mix are the most effective that match Kazzponic Sdn. Bhd. This report outlining the introduction, literature review, Theoretical framework, research methodology, analysis and interpretation of data and recommendation based on observation, company report, and interview to several employees in Kazzponic Sdn Bhd.